Hereditary Ent Disorders - Khalil Ahmed Orakzai, Azam Khan, Allah Noor, Usman Khan, Sohail Khan, Mubassir Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: ENT disorders have a significant impact on a child's development, which is assisted by changes in gene expression. Aims and objectives: The purpose of this study was to detect and research genetic ENT problems, as well as their forms and therapies. Methodology: This study was carried out at the Department of ENT Qazi Hussain Ahmad Hospital Nowshera for a period of one year from January 2020 to January 2021. The secondary methodology has been followed in this paper; Different information’s has been received that has helped to understand the objectives. Result: ENT disorder is related with genetic mis-information that is transferred from parents to children.In asia region 2.28 million individuals have reported facing visual impairment and vision loss in 2020. Over 40% of the hearing loss in adult age has also been found to stimulated by genetic disorders that are transferred from parents to children’s Conclusion: this research has illustrated that most of the ENT are curable by surgery and modern approaches.